2014
DOI: 10.1007/s12603-013-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

Dentition status, malnutrition and mortality among older service housing residents

Abstract: Edentulousness is still common among older service housing residents. Edentulousness without prosthesis was associated with poor nutritional status, oral symptoms and infrequent use of dental services. These findings suggest the need for co-operation between nursing staff and oral care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 34 publications
4
80
0
Order By: Relevance
“…Long‐term care staff perceive assisting residents with oral hygiene tasks as unpleasant, especially among residents who resist, indicating the need for staff education to manage oral hygiene in the presence of resistiveness to care among residents. Maintaining oral health and dentition status is interdisciplinary in nature and signifies cooperation between nursing and dental professionals . A team‐based approach is needed in developing and implementing oral hygiene and health interventions to improve eating performance and nutritional outcomes in residents with and without cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term care staff perceive assisting residents with oral hygiene tasks as unpleasant, especially among residents who resist, indicating the need for staff education to manage oral hygiene in the presence of resistiveness to care among residents. Maintaining oral health and dentition status is interdisciplinary in nature and signifies cooperation between nursing and dental professionals . A team‐based approach is needed in developing and implementing oral hygiene and health interventions to improve eating performance and nutritional outcomes in residents with and without cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that after 14 years of our development and educational project in institutional settings, the nurses were more aware of their residents' chewing and nutritional problems. Edentulousness and chewing problems were reported as associated with malnutrition that may lead to functional decline, disability, and reduced health‐related quality of life …”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, these results support the hypothesis that regular use of dentures might blunt the risk of earlier mortality associated with MD. 12,27 Thus, it would be advisable to include the provision of dentures as a preventive intervention in healthcare programs. Most elderly adults with dentures reported malfunctioning of the prosthesis as the cause of MD.…”
Section: Figurementioning
confidence: 99%
“…This finding is in line with previous studies that found an association between edentulism and several adverse outcomes, including cognitive and functional impairment and mortality. [26][27][28][29] Edentulism is a robust and irreversible marker of poor oral health, representing total tooth loss and reflecting longstanding, severe oral disease.…”
Section: Figurementioning
confidence: 99%